TiO2-based water-tolerant acid catalysis for biomass-based fuels and chemicals - Sudarsanam, Putla; Li, Hu; Sagar, Tatiparthi Vikram (ACS Catalysis, 2020)
Solid acid catalysts alone or in combination with redox metals play a pivotal role in biomass valorization to obtain alternative fuels and chemicals. In acid-catalyzed biomass conversions, water is a key reagent/byproduct that can induce leaching/poisoning of catalyst's acid species, a major problem toward catalyst recyclability and product purification. Thus, developing efficient water-tolerant solid acid catalysts is vital for viable biomass valorization. TiO2 is considered to be a promising water-tolerant solid acid catalyst for biomass conversions because of the presence of coordinatively unsaturated Ti4+ sites, which are robust and less prone to leaching in the aqueous medium. Besides, the synergistic combination of TiO2 with redox metals (Ru, Pd, Ni, Cu, etc.) provides abundant bifunctional acid-redox sites, which exhibit a favorable catalytic role in the deoxygenation of biomass molecules to practically useful hydrocarbons. Therefore, this review provides an overview of recent progress toward TiO2-based water-tolerant acid catalysis for biomass conversion, with a focus on hydrothermal stability of TiO2, its acidity, and catalysts' synthesis methods. Various biomass conversions over TiO2-based catalysts, where water-tolerant acid sites or acid-redox dual sites show a significant catalytic effect, were discussed. Structure-activity relationships based on water-tolerant Lewis acidity of TiO2 were emphasized. We believe that this review will provide valuable information for developing efficient water-tolerant solid acid catalysts not only for biomass valorization but also for other challenging reactions in the aqueous medium.
Keywords: Acid catalysis; acid-redox catalysis; Biomass conversion; renewable fuels and chemicals; TiO2-based catalysts; water-tolerant Lewis acidity